Wound exudate as a proteomic window to reveal different mechanisms of tissue damage by snake venom toxins - Escalante Muñoz, Teresa (2009)
In light of the complexity of wound tissue, proteomic analysis may not clearly reveal the nature of the wound or the processes involved in healing. However, exudate associated with wounds may provide a “window” on cellular events leading to the development of the wound and/or its healing. In this investigation we performed proteomic analysis on wound exudates from muscular wounds in mice caused by two very different types of snake venom toxins: BaP1, a snake venom metalloproteinase and Mtx-I, a snake venom phospholipase A2. Proteomic analysis of the exudates associated with these wounds clearly differentiated them and offered new perspectives on functional mechanisms by which these toxins cause tissue damage. In the case of wounds caused by the metalloproteinase, there was evidence of degradation of nonfibrillar collagens whereas the phospholipase wound exudate was noted by the presence of fibrillar collagen type I, apolipoproteins A-I, A-IV, and E, and fibronectin. These results suggest that the hemorrhage caused by snake venom metalloproteinases may be associated with the degradation of specific extracellular matrix proteins which play a role in matrix/capillary stabilization and that release of apolipoproteins from their complexes may be involved with the dysfunctional hemostatsis observed following snake envenoming.